Barriers to Collaborative Anesthetic Care Between Anesthesiologists and Nurses on the Labor and Delivery Unit: A Study Using Modified Delphi Technique. Issue 2 (June 2018) - Fung, L.Y.; Downey, K.; Watts, N.; Carvalho, J.C.A.
Abstract : ( Can J Anaesth . 2017;64(8):836–844) Teamwork between anesthesiologists and nurses is very important for patient safety and effective care, particularly in obstetric care. Barriers to effective teamwork between nurses and physicians are varied and can be difficult to identify, but may include lack of role clarity, intimidation and bullying, linguistic or cultural barriers, dependence on electronic systems, poor communication and hesitation to challenge the authority of the physician. The Delphi technique is a survey method used to minimize bias in group interviews and acquire a consensus of ideas from experts. This study uses a modified Delphi technique to gain consensus on the perceived barriers to collaboration between perinatal registered nurses and anesthesiologists in a tertiary labor and delivery unit.